Interest Rate Pass-Through: Mortgage Rates, Household Consumption, and Voluntary Deleveraging - Di Maggio, Marco; Kermani, Amir; Keys, Benjamin J.; Piskorski, Tomasz; Ramcharan, Rodney; Seru, Amit; Yao, Vincent (The American economic review, 2017)
Exploiting variation in the timing of resets of adjustable-rate mortgages (ARMs), we find that a sizable decline in mortgage payments (up to 50 percent) induces a significant increase in car purchases (up to 35 percent). This effect is attenuated by voluntary deleveraging. Borrowers with lower incomes and housing wealth have significantly higher marginal propensity to consume. Areas with a larger share of ARMs were more responsive to lower interest rates and saw a relative decline in defaults and an increase in house prices, car purchases, and employment. Household balance sheets and mortgage contract rigidity are important for monetary policy pass-through.